MATHEMATICS
MIDDLE SCHOOL

Answer: Area of Oven Tray = 60 * 50 = 3000

Area of Cake Tin = r²

r = 25/2 = 12.5

Area of Cake Tin = (12.5)²

= 156.25 = 490.87....

Number of Cake Tins that will fit =

Number of Cake Tins that will fit = 3000/490.87.... = 6.1115....

You can't have 0.11154.... of a tray so the answer is just 6.

Area of Cake Tin = r²

r = 25/2 = 12.5

Area of Cake Tin = (12.5)²

= 156.25 = 490.87....

Number of Cake Tins that will fit =

Number of Cake Tins that will fit = 3000/490.87.... = 6.1115....

You can't have 0.11154.... of a tray so the answer is just 6.

HIGH SCHOOL

A shoper buys 3 items for $2.99, $4.79 and 3.87 estimate the total

to estimate round the 3 values to the nearest dollar

2.99 = 3

4.79 = 5

3.87 = 4

3 + 5 +4 = 12

estimated total would be approximately $12

real total = 2.99 + 4.79 +3.87 = 11.65 ( not far off of the estimated value)

MIDDLE SCHOOL

A geometric sequence has an initial value of 18 and a common ratio of 1/2.write a function to represent this sequence

Answer:

Step-by-step explanation:

Given a geometric sequence has an initial value of 18 and a common ratio of 1:2. we have o write the function to represent this sequence.

⇒ a=18 and

The formula to find the nth term of sequence is

, where a is the first term and r is the common ratio.

⇒

The above function represent the sequence that has an initial value of 18 and a common ratio of 1:2.

MIDDLE SCHOOL

Solve 2x2 + 12x − 14 = 0 by completing the square. 2(x + 6)2 = 26; x = −6 + √13, x = −6 − √13

2(x + 6)2 = 20; x = −6 + √20, x = −6 − √20

2(x + 3)2 = 32; x = 1, x = −7 2(x + 3)

2 = 32; x = 13, x = 19

What do I do now? Can someone help me please? :/

According to my calculations, the answer would be 2(x + 3)2 = 32; x = 1, x = −7.

(hope this helps)

(hope this helps)

MIDDLE SCHOOL

What is the resultant of a and b if a = 3i + 3j and b = 3i − 3j?

Answer:

A. 6i+0j

Step-by-step explanation:

did it on edge 2020

Answer:

a + b= 6i

Step-by-step explanation:

so what you're trying to find is a+b.

a= 3i+3j

b= 3i-3j

a + b= (3i + 3j) + (3i -3j)

combine like terms

3i + 3i + 3j- 3j= 6i + 0j= 6i

So, a + b= 6i